Exposure of marine megafauna to cumulative anthropogenic threats in north-west Australia - Ferreira, Luciana C.; Thums, Michele; Whiting, Scott; Meekan, Mark; Andrews-Goff, Virginia; Attard, Catherine R. M.; Bilgmann, Kerstin; Davenport, Andrew; Double, Mike; Falchi, Fabio; Guinea, Michael; Hickey, Sharyn M.; et al. (Frontiers in Ecology and Evolution, 2023)
As the use of coastal and offshore environments expands, there is a need to better understand the exposure of marine megafauna to anthropogenic activities that potentially threaten their populations. Individual satellite telemetry studies are often hampered by small sample sizes, providing limited information on spatiotemporal distributions of migratory animals and their relationships to anthropogenic threats. We addressed this issue by synthesising satellite tracking data from 484 individuals of three taxonomic groups and six species; three marine turtle, two whale and one shark. The spatial overlap between taxa distributions and multiple anthropogenic activities was assessed as a proxy for the cumulative exposure of these taxa to anthropogenic threats (coastal modification, vessel strike, underwater noise, oil spill, bycatch, entanglement, and artificial light) across an area totalling 2,205,740 km2 off north-western Australia. Core exposure areas (top 50% of the distribution) encompassed ecologically important sites for all taxa, such as the Ningaloo and Pilbara regions, migratory routes for whales and sharks in offshore waters beyond Ningaloo Reef, and marine turtle nesting beaches at Barrow Island and Cape Lambert. Although areas of high exposure represented <14% of taxa distributions, we showed that no taxa occurred in the absence of threats and that even areas with existing spatial protections are experiencing high levels of exposure. Importantly, we developed a robust approach for documenting the potential exposure of marine species to a range of human activities at appropriate spatial scales to inform conservation management.